2015
DOI: 10.1111/ene.12746
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renin‐angiotensin system blockade on clinical outcome in glioblastoma

Abstract: Treatment with Ang-II inhibitors in combination with RT and TMZ might improve clinical outcome in GBMs. Prospective trials are needed to test this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Blockade of the RAS leads to inhibited growth of colorectal cancer liver metastases in the regenerating liver [33] and recent reports of increased overall survival of GB patients treated with angiotensin receptor blockers [34] , support the role of the RAS in cancer. It is exciting to speculate that CSCs in MM to the brain maybe a novel therapeutic target by modulating the RAS, although more work including a larger sample size, control tissue samples and in vitro and in vivo functional work is needed to determine the precise role of the RAS in this aggressive cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Blockade of the RAS leads to inhibited growth of colorectal cancer liver metastases in the regenerating liver [33] and recent reports of increased overall survival of GB patients treated with angiotensin receptor blockers [34] , support the role of the RAS in cancer. It is exciting to speculate that CSCs in MM to the brain maybe a novel therapeutic target by modulating the RAS, although more work including a larger sample size, control tissue samples and in vitro and in vivo functional work is needed to determine the precise role of the RAS in this aggressive cancer.…”
Section: Discussionmentioning
confidence: 85%
“…shown that selective synthetic renin inhibitors decrease DNA synthesis and induce apoptosis in GB cells (Juillerat-Jeanneret, Celerier et al 2004), and that ARBs are associated with statistically improved progression-free survival and overall survival in 81 patients with GB (Januel, Ursu et al 2015).…”
Section: Repurposing Drugs That Target the Rasmentioning
confidence: 99%
“…Local RAS plays a pivotal role for the tissue function both physiologic and pathophysiologic conditions based on paracrine and autocrine impacts of it [26]. RAS also modulate the body metabolic process [18].…”
Section: The Function Of Local Renin-angiotensin Systems In the Livermentioning
confidence: 99%